Pilot trial of three pine species at Caspian eastern littoral of Iran - Sayfollah Khorankeh; Hosayn Sardabi; Sayyed Ali Mosazadeh; Hosayn Barimany; Abdorreza Dehbandy (تحقیقات جنگل و صنوبر ایران, 2006)
The aim of the study was to introduce the best pine species in respect to growth and wood production for eastern coastal lands of Caspian region of Iran (Mazandaran province).  The trial was conducted in 1997 under randomized complete blocks statistical design with three replicates and three treatments, including P. pinea, P. brutia and P. longifolia. Every plot contained 121 seedlings at spacing of 3 x 3 m. The measured growth characteristics were as follows: survival, collar diameter, height, diameter increment, height increment and quality. The growth parameters were evaluated annually end of growth period.  After five years, the data were analyzed by ANOVA and Duncan tests, using SPSS and SAS softwares. The results show that although there was not significant difference between the species in respect to survival, collar diameter and diameter increment, but there was significant difference in respect to their height, height increment and quality. The highest and the lowest values of height parameter belonged to P. brutia and P. longifolia, respectively. The most promising species was P. brutia which achieved 159.1 cm total height and 25.91 cm height increment, five years after planting.